2011
DOI: 10.1007/s10384-011-0053-z
|View full text |Cite
|
Sign up to set email alerts
|

Posterior syphilitic uveitis: clinical characteristics, co-infection with HIV, response to treatment

Abstract: In this series, syphilitic posterior uveitis presented only in men, and all with available data were MSM. The majority were concomitantly infected with HIV. Clinical presentations varied and all patients demonstrated either significant improvement or complete resolution of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…Coinfection of syphilis and HIV was only observed in one patient, and the sexual history was difficult to assess in our study because of traditional Chinese customs. Compared with other reports [4, 10], the frequency of co-infection of HIV in our patients with syphilitic uveitis was much lower, which may be due to the low prevalence of HIV in China, especially in northern China [16]. There were more female patients than male patients in our cohort.…”
Section: Discussioncontrasting
confidence: 73%
“…Coinfection of syphilis and HIV was only observed in one patient, and the sexual history was difficult to assess in our study because of traditional Chinese customs. Compared with other reports [4, 10], the frequency of co-infection of HIV in our patients with syphilitic uveitis was much lower, which may be due to the low prevalence of HIV in China, especially in northern China [16]. There were more female patients than male patients in our cohort.…”
Section: Discussioncontrasting
confidence: 73%
“…Recent reports by Fonollosa et al and Li et al noted high rates of HIV co-infection (70-80%) and it has been proposed that the era of highly active anti-retroviral therapy (HAART) with prolonged survival of HIV-positive patients might have contributed to the rising rates of syphilitic uveitis. 13,24 Taking into account the 2 patients who declined HIV testing, our possible range of HIV co-infection would be 25.0-41.2%, which is lower than that quoted in previous studies. In an earlier local case series from Singapore, Chio et al reported no patients with concomitant HIV co-infection.…”
Section: Discussionmentioning
confidence: 55%
“…Similar studies of posterior segment manifestations have shown great variability in the distribution of these findings. 13,14 Posterior placoid chorioretinitis, a characteristic but not pathognomonic feature of syphilitic posterior uveitis, was present in both eyes of one of our HIV-negative patients (patient 7). Characteristic fine pigmented changes within a circumscribed lesion that demonstrated disk leakage and paramacular choroidal hypofluoresence on fluorescein angiography were seen.…”
Section: Discussionmentioning
confidence: 70%
“…Antibacterial agents were used as monotherapy in 286 patients in 15 studies [14, 17, 20, 23, 27, 30, 34, 35, 37, 39, 40, 4245]. The mean age of the patients ranged from 37 to 58 years.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [17, 21, 22, 24, 27, 28, 30, 36] involving 190 patients (318 eyes) reported ocular complications that included cataract ( n = 41), ocular hypertension ( n = 15), posterior synechiae ( n = 15), chorioretinal scarring ( n = 12), epiretinal membrane ( n = 12), macular edema ( n = 10), optic disc atrophy ( n = 10), and retinal detachment ( n = 8) (Table 5). …”
Section: Resultsmentioning
confidence: 99%